Efeitos de confinamento quântico em nanoestruturas quase unidimensionais de carbono investigados por espalhamento Raman ressonante - Viviane Valquíria do Nascimento (2022)
This work was focused on the study of confinement effects in optical properties of quasi-one dimensional structures: armchair graphene nanoribbons and sulfur chains encapsulated by single wall carbon nanotubes. We performed resonant Raman scattering experiments over 7 and 9 atoms wide armchair graphene nanoribbons, named 7AGNRs and 9AGNRs. Exposed to air, in room conditions, graphene nanoribbons quickly degraded under laser excitation. We found that under a nitrogen atmosphere at 80K, the degradation process slowed down, allowing us to obtain the Raman excitation profile (REP) for both samples. Thus we found that the 7AGNRs exhibit optical transition energies at 2.26 and 2.51 eV, and the 9AGNRs showed transitions energies at ≈1.4, 2.38 e ≈2.78 eV. The linear sulfur chains are unstable in room conditions. However they can be synthesized inside the carbon nanotubes by sulfur vapor. The resulting hybrid system shown a giant Raman signal for the sulfur chains encapsulated by HiPco carbon nanotubes. Furthermore, the Raman modes assigned to the encapsulated chains exhibit a resonant behavior for excitation energies between 1.91 and 2.81 eV. Thereby, in this work we have obtained the Raman excitation profile for the sulfur chains encapsulated by HiPco single walled carbon nanotubes, which showed resonance energies at 2.35 and 2.59 eV. From Kataura plot information about transition energies related to the nanotubes diameters and the radial breathing modes observed in the sample, we concluded that the giant Raman signal is due to a specific interaction between the nanotubes (8,5) and the vibrational modes of the sulfur chain in this confined environment.